1984
DOI: 10.3171/jns.1984.60.4.0803
|View full text |Cite
|
Sign up to set email alerts
|

Arachnoid cysts of the Sylvian fissure

Abstract: Morphological and enzyme ultracytochemical evidence is presented to support the contention that the walls of arachnoid cysts secrete fluid. Clinical evidence has already suggested this phenomenon, including intracranial pressure elevation and expansion in some cases, and the observation that arachnoid cysts constitute closed compartments with a fluid content that cannot be derived from other cerebrospinal fluid-containing spaces. Ultrastructurally, the cyst lining showed a similarity to subdural neurothelium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0
6

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(66 citation statements)
references
References 51 publications
1
59
0
6
Order By: Relevance
“…24 Finally, data from some studies have shown that the membranes of arachnoid cysts harbor secretory properties that may be partially responsible for their potential to expand. 9 In any case, progressive growth of arachnoid cysts may cause secondary regional effects such as hypoplasia of the temporal lobe as well as manifest as symptoms such as seizures, developmental delay, visual loss, or motor deficits. 6,7,22,29 Patients with arachnoid cysts may also present with hemorrhagic events, especially following head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…24 Finally, data from some studies have shown that the membranes of arachnoid cysts harbor secretory properties that may be partially responsible for their potential to expand. 9 In any case, progressive growth of arachnoid cysts may cause secondary regional effects such as hypoplasia of the temporal lobe as well as manifest as symptoms such as seizures, developmental delay, visual loss, or motor deficits. 6,7,22,29 Patients with arachnoid cysts may also present with hemorrhagic events, especially following head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed, including active fluid secretion by cells in the cyst wall, expansion after formation of an osmotic gradient, and unidirectional valve mechanisms. 4,7,16,19 Cyst growth can lead to clinically important symptoms through increased intracranial pressure and/or compression of surrounding brain structures, including a CSF flow pathway. Symptoms can also arise suddenly after cyst rupture or hemorrhage into a cyst, and for both cases (cyst growth and cyst rupture/ hemorrhage), symptom type and severity tend to depend on cyst location.…”
mentioning
confidence: 99%
“…The cyst enlargement seems to be the result of secretory activity of the arachnoid cells lining the cyst, 19 but other mechanisms such as infiltration across osmotic gradient and unidirectional flow through a ball-valve arrangement have also been considered. 20 The clinical manifestations of arachnoid cysts are variable and often unspecific. 14,[21][22][23][24][25][26] The most common presenting symptoms and signs are those of raised intracranial pressure, craniomegaly, and developmental delay.…”
Section: Discussionmentioning
confidence: 99%